Not a pretty picture. (Economist, 2019)
The article explores the operation of Nvidia, a U.S. firm that manufactures graphics-processing units (GPUs), amid the rising chip-design business. It attributes the industry trend to the shift to cloud computing and the rise of specialized computing tasks such as artificial intelligence (AI). However, Nvidia reported declines in their revenue and lower share prices.